An arbuscular mycorrhizal fungus significantly modifies the soil bacterial community and nitrogen cycling during litter decomposition - Erin E. Nuccio; Angela Hodge; Jennifer Pett‐Ridge; Donald J. Herman; Peter K. Weber; Mary K. Firestone (Environmental Microbiology, 2013)
Summary Arbuscular mycorrhizal fungi ( AMF ) perform an important ecosystem service by improving plant nutrient capture from soil, yet little is known about how AMF influence soil microbial communities during nutrient uptake. We tested whether an AMF modifies the soil microbial community and nitrogen cycling during litter decomposition. A two‐chamber microcosm system was employed to create a root‐free soil environment to control AMF access to 13 C ‐ and 15 N ‐labelled root litter. Using a 16 S rRNA gene microarray, we documented that approximately 10% of the bacterial community responded to the AMF , G lomus hoi . Taxa from the F irmicutes responded positively to AMF , while taxa from the Actinobacteria and Comamonadaceae responded negatively to AMF . Phylogenetic analyses indicate that AMF may influence bacterial community assembly processes. Using nanometre‐scale secondary ion mass spectrometry ( NanoSIMS ) we visualized the location of AMF ‐transported 13 C and 15 N in plant roots. Bulk isotope ratio mass spectrometry revealed that the AMF exported 4.9% of the litter 15 N to the host plant ( P lantago lanceolata L .), and litter‐derived 15 N was preferentially exported relative to litter‐derived 13 C . Our results suggest that the AMF primarily took up N in the inorganic form, and N export is one mechanism by which AMF could modify the soil microbial community and decomposition processes.